2013
DOI: 10.1002/jcph.195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dosing schemes of amoxicillin on eradication rates of Helicobacter pylori with amoxicillin‐based triple therapy

Abstract: The dosing scheme of amoxicillin significantly influenced eradication rates of triple therapies. Although amoxicillin is empirically dosed twice daily, amoxicillin should be dosed at least three times daily in amoxicillin-based triple therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 23 publications
1
45
1
Order By: Relevance
“…Recent studies from Japan have demonstrated that the eradication rates in clarithromycin-based triple regimens with qid dosing of amoxicillin were higher than those of regimens with the bid dosing of amoxicillin about 14% (91.9% and 77.8% respectively.) (Furuta et al, 2014). The data on the effectiveness of the dosing scheme of amoxicillin triple therapy with clarithromycin-containing regimen in Thailand are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies from Japan have demonstrated that the eradication rates in clarithromycin-based triple regimens with qid dosing of amoxicillin were higher than those of regimens with the bid dosing of amoxicillin about 14% (91.9% and 77.8% respectively.) (Furuta et al, 2014). The data on the effectiveness of the dosing scheme of amoxicillin triple therapy with clarithromycin-containing regimen in Thailand are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent study has demonstrated the positive effect of the dosing scheme of amoxicillin significantly influenced eradication rates of triple therapies. Eradication rates in regimens with tid and qid dosing of amoxicillin were higher than those of regimens with the bid dosing of amoxicillin (Furuta et al, 2014). One of the popular present first-line treatment options is sequential regimen, which has shown higher eradication rates than conventional triple therapy in several recent meta-analyses (Zullo et al, 2007;Jafri et al, 2008;Gatta et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial action of AMPC depends on the ratio between dosing interval and time over MIC (% Time-above MIC). For an AMPC insensitive strain, the shortening of % Time-above MIC due to an increase in the MIC is the cause of failure to eradicate H. pylori [44].…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent study has also reported a seasonal variation in EoE-related food impaction, 7 food impaction is usually a consequence of the fibrotic oesophageal remodelling in patients with long-standing EoE. 6 Likewise, food impaction during outdoor seasons might also be related to different food and social behaviours during holidays. EoE patients are usually sensitised to indoor perennial aeroallergens 8 and de novo onset of EoE has been associated with exposure to mould and dust.…”
Section: Acknowledgementmentioning
confidence: 99%
“…An EoE diagnosis is established in symptomatic patients after upper endoscopy with oesophageal biopsies. Diagnostic delay since the onset of symptoms is extremely common, 6 due to variables related to patients (underestimation of symptoms, avoidance of medical attention or eating behaviour modifications), physicians (lack of suspicion, lack of biopsies during endoscopy) and hospitals (waiting time for endoscopy). As such, equating the onset of clinical manifestations, potentially triggered by seasonal aeroallergens, with the time of performance of the endoscopy may be inaccurate.…”
Section: Acknowledgementmentioning
confidence: 99%